Wine and Gastronomic Tourism in the Drama Region - Aikaterini Karampatea; Spyridon Mamalis; Elisavet Bouloumpasi; Adriana Skendi; Irene (Eirini) Kamenidou (Tourism and Hospitality)
Drama is a wine region in northern Greece with a local economy based on agricultural production. Despite its historical and geographical setting, the wine tourism industry is not very well developed in the wine-growing region of Drama. Although the sustainability of territorial development is often linked to local food and wine heritage, it seems that the implicated parties are not totally convinced. For this qualitative case study, we first conducted interviews with the management of the local wineries to determine the reason behind the low number of wine tourists in the area. Then, a workshop was organized, and all relevant parties were invited to increase awareness through education while also attempting to find mutually agreeable solutions through working group table discussions and the presentation of findings. Taking advantage of and preserving the cultural heritage through the cooperation of the related regional businesses, regional/central authorities, and non-governmental organizations (NGOs) was concluded to be an important tool for organizing new initiatives that will boost wine tourism.